Mesenchymal stem cells mediate the clinical phenotype of inflammatory breast cancer in a preclinical model. Issue 1 (December 2015) - Lacerda, Lara; Debeb, Bisrat; Smith, Daniel; Larson, Richard; Solley, Travis; Xu, Wei; Krishnamurthy, Savitri; Gong, Yun; Levy, Lawrence; Buchholz, Thomas; Ueno, Naoto; Klopp, Ann; et al.
Abstract Introduction Inflammatory breast cancer (IBC) is an aggressive type of breast cancer, characterized by very rapid progression, enlargement of the breast, skin edema causing an orange peel appearance (peau d'orange ), erythema, thickening, and dermal lymphatic invasion. It is characterized by E-cadherin overexpression in the primary and metastatic disease, but to date no robust molecular features that specifically identify IBC have been reported. Further, models that recapitulate all of these clinical findings are limited and as a result no studies have demonstrated modulation of these clinical features as opposed to simply tumor cell growth. Methods Hypothesizing the clinical presentation of IBC may be mediated in part by the microenvironment, we examined the effect of co-injection of IBC xenografts with mesenchymal stem/stromal cells (MSCs). Results MSCs co-injection significantly increased the clinical features of skin invasion and metastasis in the SUM149 xenograft model. Primary tumors co-injected with MSCs expressed higher phospho-epidermal growth factor receptor (p-EGFR) and promoted metastasis development after tumor resection, effects that were abrogated by treatment with the epidermal growth factor receptor (EGFR) inhibitor, erlotinib. E-cadherin expression was maintained in primary tumor xenografts with MSCs co-injection compared to control and erlotinib treatment dramatically decreased this expression in control and MSCs co-injected tumors. Tumor samples from patients demonstrate correlation between stromal and tumor p-EGFR staining only in IBC tumors. Conclusions Our findings demonstrate that the IBC clinical phenotype is promoted by signaling from the microenvironment perhaps in addition to tumor cell drivers.